The Effectiveness of Implementing Youtube Media In Improving Speaking Skills By Acehnese Teachers - Asnawi Muslem; Ika Apriani Fata; Saiful Marhaban; Yulianti Yulianti (Proceedings of AICS - Social Sciences, 2021)
The development of information and communication technology (ICT) has become part of our lives today and has attracted the attention of many parties. Learning activities have as well been facilitated, but not many who made use of it. One of the ICT products is YouTube which is a sharing video site for various purposes. The materials presented by YouTube can be used to support learning in schools. This paper tries to explore the role of YouTube in supporting the English speaking skill. N=5 Young Acehnese English teachers (Age=23-28) and N=153 students were participating in this research. The results revealed that the speaking skill of experimental class increased especially in the comprehension aspect. Thus, the teachers may consider implementing online media such as Youtube to promote the students’ speaking skill accordingly.Keywords: Youtube, Media, Students’ speaking skill, Aceh